Introduction to Islamic Economics for Micro, Small, And Medium Enterprises (MSMEs) - Devi Imelda Safitri Hasibuan; Aminah Rahman Daulay; Robiatul Adawiyah; Rondom Tanjung; Anugerah, Tirta (CV. Ulil Albab Corp, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are a major pillar of the Indonesian economy, yet they still face various fundamental problems, particularly limited financial literacy and access to fair and sustainable financing. Amidst the development of the sharia economy in Indonesia, the introduction of sharia economic principles is seen as a strategy for empowering MSMEs that has the potential to strengthen business sustainability. However, in practice, many MSMEs still have a limited understanding of the concept of sharia economics and have not yet implemented it optimally in business management. This study aims to examine in depth the introduction of sharia economics among MSMEs, specifically regarding the level of understanding, financial management practices, and access to and perceptions of sharia financing. The research method used is a qualitative approach with descriptive characteristics. Data were collected through observation, interviews, and document searches, then analyzed using qualitative descriptive analysis through the stages of data reduction, data presentation, and drawing conclusions. The results show that most MSMEs still have a simple understanding of sharia economics, have not implemented systematic financial records, and face obstacles in accessing sharia financing. However, MSMEs that received Islamic economic education and mentoring demonstrated positive changes in financial behavior, business transparency, and readiness to access Islamic financing. These findings confirm that the introduction of Islamic economics through ongoing education and mentoring plays a crucial role in strengthening the capacity and sustainability of MSMEs.